**Q) Solve the following pair of linear equations:**

**Ans: **

Given the equations:

……….. (i)

………….(ii)

**Step 1:** Let’s multiply equation (i) by b^{2 }and add to equation (ii), we get:

……….. (i)

∴ ……….. (i)

∴ ……….. (i)

∴ b^{2} x + a^{2} x = a ( a^{2} + b^{2} )

∴ x (a^{2} + b^{2 }) = a ( a^{2} + b^{2} )

**∴ x = a**

**Step 2:** Lets substitute x = a in equation (ii) and we get:

a x + b y = a^{2 }+ b^{2}

∴ a (a) + b y = a^{2 }+ b^{2}

∴ a^{2} + b y = a^{2 }+ b^{2}

∴ b y = b^{2}

**∴ y = b**

**Therefore, x = a and y = b**

**Please do press “Heart” button if you liked the solution.**